Protective Effect of γ-Aminobutyric Acid Against Chilling Stress During Reproductive Stage in Tomato Plants Through Modulation of Sugar Metabolism, Chloroplast Integrity, and Antioxidative Defense Systems - Abd Elbar, Ola H.; Elkelish, Amr; Niedbała, Gniewko; Farag, Reham; Wojciechowski, Tomasz; Mukherjee, Soumya; Abou-Hadid, Ayman F.; El-Hennawy, Hussien M.; Abou El-Yazied, Ahmed; Abd El-Gawad, Hany G.; Azab, Ehab; Gobouri, Adil A.; et al. (Frontiers in Plant Science, 2021)
Despite the role of γ-aminobutyric acid (GABA) in plant tolerance to chilling stress has been widely discussed in the seedling stage, very little information is clear regarding its implication in chilling tolerance during the reproductive stage. Here, we investigated the influence of GABA (1 and 2 mM) as a foliar application on tomato plants (Solanum lycopersicum L. cv. Super Marmande) subjected to chilling stress (5 °C for 6 h/day) for successive 5 days during the flowering stage. The results indicated that applied GABA differentially influenced leaf pigment composition by decreasing the chlorophyll a/b ratio and increasing the anthocyanin in relative to total chlorophyll. However, carotenoids were not affected in both GABA-treated and non-treated stressed plants. Interesting correlations were obtained between GABA-induced upregulation of sugar metabolism coinciding with the integrity of plastids’ ultrastructure. Root tissues significantly exhibited an increase in thermo-tolerance in GABA-treated plants. Furthermore, applied GABA substantially alleviated the chilling induced oxidative damage by protecting cell membrane integrity and reducing malondialdehyde (MDA) and H2O2. This positive effect of GABA was associated with enhancing the activity of phenylalanine ammonia-lyase (PAL), catalase (CAT), superoxide dismutase (SOD), and ascorbate peroxidase (APX). Conversely, a downregulation of peroxidase (POX) and polyphenol oxidase (PPO) was observed under chilling stress, indicating its relevance in phenol metabolism. Eventually, applied GABA especially at 2 mM improved the fruit yield and could be recommended to mitigate the damage of chilling stress in tomato plants.